Validación de métodos de control de enfermedades fungosas y malezas en el cultivo de arroz (Oryza sativa L.) sobre variables de crecimiento y rendimiento, en el cantón Macará, provincia de Loja - Arevalo Gallo, Cesar Steve (2024)
In Ecuador, rice is a staple food and a crop of great socioeconomic importance. In 2020, national production was 1,336,502 tons, of which the province of Loja, in the southern region, contributed 78,059 tons. However, the inappropriate use of chemicals to control fungal diseases and weeds has reduced crop yields. Lack of training in sustainable practices and integrated management has aggravated the problem, causing resistance and affecting soil health and product quality. Therefore, it is crucial to educate farmers and promote responsible agricultural practices. This research focused on identifying the growth and yield response of rice using different fungal disease and weed control methods. A completely randomized experimental design (CRD) with bifactorial arrangement was used, evaluating growth variables such as weed diversity, plant height and number of tillers. For yield, grain spotting, empty kernels, number of panicles, 1000 kernel weight, number of kernels per panicle, yield, harvest index and milling quality were evaluated. The results showed that weed diversity was most favorable 30 days after transplanting. In terms of height, the herbicide Florpyrauxifen-benzyl + Cyhalofop-butyl and the fungicide Difenoconazole + Pyraclostrobin - Azoxystrobin + Tridemorph reached the best heights (95.32 cm and 93.60 cm, respectively). Treatment T6 was superior in number of tillers (25.3) and panicles (13.30). In addition, Difenoconazole + Pyraclostrobin - Azoxystrobin + Tridemorph achieved a better control of grain spotting (2.17 %) and empty kernels (1.01 %). Although there were no significant differences in 1000-grain weight, yield and milling quality improved with Difenoconazole + Pyraclostrobin - Azoxystrobin + Tridemorph, highlighting its efficacy in disease control and crop yield